Identification of mothers with mental health problems is accidental: perceptions of health care providers on availability, access, and support for maternal mental health care for adolescent mothers in Malawi - Chimwemwe Tembo; Linda Portsmouth; Sharyn Burns (BMC, 2024)
Abstract Background Integration of maternal mental health into primary health care is considered a strategy to improve access to mental health support in low- and middle-income countries (LMICs). Health care workers' (HCWs) and traditional practitioners' (traditional healers, herbalists, traditional birth attendants, spiritual healers, prophets, and community health volunteers) perceptions of the availability and management of adolescent mothers' maternal mental health care were explored in rural Malawi. Recognizing and identifying the barriers associated with access to maternal mental health support is essential to improving the mental health of adolescent mothers. Methods A descriptive qualitative design (DQ) was used to explore HCWs' and traditional practitioners' perceptions of maternal mental health services for adolescent mothers. In-depth interviews were conducted with HCWs (n = 6), and three focus group discussions were conducted with 30 community-based traditional practitioners. Participants were purposefully recruited because they provide formal or informal health services to adolescent mothers during the postnatal period at Mitundu Rural Hospital and its catchment area in Lilongwe District, in Malawi. Interviews were analyzed using reflective thematic analysis and inductive thinking. Results Thematic analysis found four themes to describe access to maternal mental health care for adolescent mothers. Participant perceptions were themed around health system challenges and how cultural background and beliefs influence access to mental health care and support. The themes were: (1) Inadequate staff development; (2) Limited resources (medication and infrastructure); (3) Limited policy and guidelines implementation; and (4) Cultural background and belief influence on help-seeking. HCWs suggested improving pre-service and in-service training to improve mental health assessment of mothers, while traditional practitioners wanted to increase their awareness of mental health issues. Conclusion Participants emphasized that multifaceted factors influenced access to mental health support. These factors affect the assessment, treatment, and support of adolescent mothers and help-seeking by mothers. Therefore, strengthening the healthcare system and empowering providers with the knowledge and skills to recognize at-risk mothers and provide timely support is essential.